Framing Produser pada Proses Produksi Program Pentas Ceria Lembaga Penyiaran Publik Lokal (LPPL) TV Peduli Kota Parepare - Muliani, Rina Yustika (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This thesis discusses the framing by producers in the production process of a TV program. The first problem statement is about how the production process of the